Implementasi Filsafat Pragmatisme William James dalam Proses Pendidikan Agama Kristen - Heeng, Go; Zega, Yunardi Kristian; Pandie, Remegises Danial Yohanis; Gea, Kariaman (Sekolah Tinggi Teologi Sumatera Utara, 2023)
The purpose of writing this article is to discuss William James's philosophy of pragmatism and its implementation in the process of Christian religious education. This paper refers to the framework of William James's philosophical theory and its urgency for education, specifically Christian religious education. James emphasizes the importance of the practical application of ideas and concepts, and that the value of an idea can be measured by its practical consequences in action. James also emphasized the importance of experience in the learning process, and that experience should be used as a starting point in achieving a deeper understanding. By using the literature study method, researchers found that William James' theory can be implemented in the process of Christian religious education because it provides learning experiences through values that are democratic, social and changes in learning patterns through learning methods, the role of the teacher, the role of students and the contextual curriculum. AbstrakTujuan penulisan artikel ini adalah membahas filsafat pragmatisme William James dan implementasinya dalam proses pendidikan agama Kristen. Tulisan ini mengacu pada kerangka teori filsafat William James dan urgensinya bagi pendidikan, secara khusus pendidikan agama Kristen. James menekankan pentingnya aplikasi praktis dari gagasan dan konsep, dan bahwa nilai dari sebuah gagasan dapat diukur oleh konsekuensi praktiknya dalam tindakan. James juga menekankan pentingnya pengalaman dalam proses pembelajaran, dan bahwa pengalaman harus dijadikan sebagai titik awal dalam mencapai pemahaman yang lebih dalam. Dengan menggunakan metode studi pustaka, peneliti menemukan bahwa teori William James dapat di implementasikan dalam proses pendidikan agama Kristen karena memberikan pengalaman belajar melalui nilai-nilai yang bersifat demokratis, sosial dan perubahan pola belajar melalui metode belajar, peran guru, peran siswa serta kurikulum kontekstual.